Influencing the environmental stress cracking resistance of amorphous thermoplastic parts by the example of polycarbonate and water. (14th November 2018) - Hopmann, Christian; Borchmann, Nikolai; Koch, Simon; Alperstein, David
Abstract : Plastic components in use are often exposed to a large number of influences which strongly affect the functionality of the component and are often the main cause of their failure. Here, the environmental stress cracking (ESC) is considered as the main cause for the failure of plastics. Until now, there are only a few possibilities on how to predict the ESC resistance of a plastics component in use and the engineer is often confronted with this failure after the product development process is already completed. This investigations deal with that problem and it is shown how the stress cracking resistance of plastics can be influenced according to the already completed product development by the example of polycarbonate under the influence of water. The focus is on the targeted influencing of the internal part properties, the influence of additional fiber reinforcement and as a last option the selection of a new material under the elimination of elaborate experiments using molecular dynamics simulations. POLYM. ENG. SCI., 59:E361–E366, 2019. © 2018 Society of Plastics Engineers